2014
DOI: 10.1128/iai.02462-14
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Cellular Immune Responses in Cattle following Escherichia coli O157:H7 Colonization

Abstract: ؉ and ␥␦ T cells from both PT21/28-and PT32-challenged calves following ex vivo restimulation with T3SPs. This study demonstrates that cattle mount cellular immune responses during colonization with EHEC O157: H7, the temporality of which is strain dependent, with further evidence of strain-specific immunomodulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 86 publications
3
38
0
Order By: Relevance
“…The up-regulation of CD36 (log2 fold change: 4.1) was reported to increase T-cell proliferation i n vitro 43 ; GPAM , also known as GPAT-1 , (log2 fold change: 2.4) was reported to increase T-cell proliferation in mice 44 . These findings are in agreement with previous findings that increased expression of genes involved in the proliferation of T-cells in the rectum of E. coli O157 challenged cattle 45 . However, different from our previous transcriptomic analysis of rectal tissues which suggested a potential decrease in both humoral and cell-mediated immune functions in SS 11 , our current study indicates potentially enhanced T-cell migration and proliferation at the distal jejunum and descending colon of SS.…”
Section: Discussionsupporting
confidence: 93%
“…The up-regulation of CD36 (log2 fold change: 4.1) was reported to increase T-cell proliferation i n vitro 43 ; GPAM , also known as GPAT-1 , (log2 fold change: 2.4) was reported to increase T-cell proliferation in mice 44 . These findings are in agreement with previous findings that increased expression of genes involved in the proliferation of T-cells in the rectum of E. coli O157 challenged cattle 45 . However, different from our previous transcriptomic analysis of rectal tissues which suggested a potential decrease in both humoral and cell-mediated immune functions in SS 11 , our current study indicates potentially enhanced T-cell migration and proliferation at the distal jejunum and descending colon of SS.…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, it has been observed that EHEC as wells as EPEC strains could suppress NF-κB and MAPK activation as well as IκB degradation, [13] and could inhibit the production of proinflammatory cytokines IL-8 and IL-6, early in the infection by different LEE- and non-LEE encoded effectors (Tir, NleB, NleC, NleD, NleE, NleH1 and NleH2) [14]. Clearance of EHEC O157 is associated with an up-regulation of Th-1 associated transcripts within the rectal mucosa, the principle site of colonization [10, 15], suggesting that a cellular component of the adaptive immune response may be important in EHEC O157 control.…”
Section: Introductionmentioning
confidence: 99%
“…To date there has been little empirical research on the interaction between F. hepatica and VTEC O157 in cattle. Recent evidence suggests a role for type 1 immune responses in control of VTEC O157 in cattle, with clearance of the bacteria from the bovine intestine associated with an up-regulation of T-helper type 1 associated transcripts within the rectal mucosa, the principle site of colonisation by this bacteria ( Corbishley et al, 2014; Naylor et al, 2003 ). On the other hand, F. hepatica is known to suppress type 1 immune responses and induce an anti-inflammatory or regulatory immune environment in the host ( Brady et al, 1999; Flynn et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%